Alternatives to methyl bromide in vegetable and strawberry crops in spain - Cebolla, Vicent (European Communities, 2022)
Alternatives to Methyl bromide (MB) have been studied in seven locations along the whole Valencian country (Spain). Among the treatments was a dosage reduction of MB by VIF sheet or 50% mixture with chloropicrin, two mixtures of 1,3-dichloropropene and chloropicrin, 32.7% and 52.8%, double treatment with 1,3-dichloropropene followed by metam-Na (MS), basamid, manure and solarization combined with manure, MS or ammonium fertilisers. Strawberry, pepper, artichoke, potato, watermelon, onion, and earth almond are among the crops grown after disinfestation. Soil sickness, Phytophthora capsici, Fusarium oxysporum, Sclerotinia minor and Verticillium dahliae were the soil problems to be controlled. Dosage reduction of MB were very good treatments but they will not be allowed after 2005 phase out except for critical uses. The mixture 1,3-dichloropropene and chloropicrin seemed a good chemical alternative if the application technique and soil preparation was done carefully, in heavy soils this treatment was sensitive to compaction. Basamid and MS did not produce good results comparable to MB, in any experiment, but it was always better than the control. High rates of organic matter amendment produced phytotoxicity in this kind of soil at the used rates. Solarization with manure is a good alternative if the manure is moderated to mininise the risk of water table contamination. The best option seemed to be rotation alternatives to maintain yield.